History Of the Novel and Its Importance as A Genre - Jurayeva Shalolakhon Khusanboyevna (Genius Journals, 2022)
This article is about the genre of the novel, its history, its place in literature, its impact on the spirituality of people, its impact on the psyche of readers, the psyche of the period, the image of the heroes
Keywords: Novel; genre; historical principl; psyche of the period